Hasrat Nadjib Al Kailani melalui Cerpen Abu Ma’Zi, Calon Pengantin Yang Sia-Sia, dan Tragedi Berdarah Di Damsyik. - Siti Hardiyanti Amri (Al-Tsaqafa : Jurnal Ilmiah Peradaban Islam, 2017)
Najib Al Kailani is a prominent Egyptian author who constantly raises social and religious issues through his works. He puts great attention to marginal people. This research aims to identify the manifestation of the subject's desires (author) presented with metaphors and metonyms in the short stories of Abu Ma'zi, Calon Pengantin Yang Sia-Sia and Tragedi Berdarah di Damsyik using Lacan's Psychoanalysis theory. Data analysis method are identifying the subject's desires through the point of view of characters, identifying the subject' lackness which encourages the desire for object a, then determining the narcissistic and the analytic desire of the subject. The research result shows that a number of characteristics, the struggle and rebellion of the characters Abu Ma'zi, Ibrahim, and Ibn Taimiyah in the short stories are the metaphor of the life of the author. A set of identity markers of these characters is the ideal ego image which becomes Najib's desire.